Pengaruh Rasio Keuangan terhadap Alokasi Belanja Modal pada Kabupaten/Kota di Provinsi Jawa Barat - Aulia Azzahra; Sudrajat (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research is done to shows the finantial ratio on capital expenditures allocation in places around West Java during 2014-2019. The ratios used are PAD effectiveness ratio, efficiency ratio, and financial dependency ratio. Financial performance is calculated using these financial ratios which later will be used as decision making in economic, political and social terms. Quantitative descriptive method is used for this research. Sampling technique in this research is using a nonprobability sampling with saturated sampling technique where the entire population is sample, which is 27 districts and cities in West Java Province. The information we used is panel data and taken from the realization of revenues and expenditures report in several places around West Java Province. The analyzing data is using the multiple linear method by Eviews software regression.